Home-Based Virtual Reality Training for Enhanced Balance, Strength, and Mobility Among Older Adults With Frailty: Systematic Review and Meta-Analysis - Hammad Alhasan; Elaf Alandijani; Lara Bahamdan; Ghofran Khudary; Yara Aburaya; Abdulaziz Awali; Mansour Abdullah Alshehri (JMIR Serious Games)
Abstract BackgroundFrailty is a geriatric syndrome associated with increased risk of falls, hospitalization, and reduced quality of life. Traditional exercises may be unsuitable for older adults with frailty due to mobility issues and accessibility barriers. Virtual reality (VR) offers an engaging, home-based alternative by providing interactive training with real-time feedback. VR interventions have shown potential benefits for improving balance, strength, and mobility. ObjectiveThis systematic review and meta-analysis aimed to evaluate the effectiveness of VR-based home training programs in improving balance, strength, and mobility among older adults with frailty and prefrailty. MethodsA systematic search was conducted in PubMed, Scopus, and Web of Science from inception to November 1, 2023, using terms related to older adults, frailty, virtual reality, balance, mobility, and strength. Eligible studies included randomized and nonrandomized trials involving adults with frailty or prefrailty aged ≥65 years who received home-based VR interventions aimed at improving balance, strength, or functional mobility. Comparator groups included no intervention, traditional exercise, or standard care. Studies involving participants with neurological or cognitive disorders were excluded. Study quality was assessed using the Physiotherapy Evidence Database scale. A random-effects meta-analysis was performed to calculate pooled mean differences (MD) and 95% CIs for 3 primary outcomes: Berg Balance Scale, Timed Up and Go, and Chair Stand. ResultsA total of 1063 records were identified, with 1023 screened after duplicate removal. Six studies met the inclusion criteria, involving 407 participants (mean age 75.2, SD 6.4 y), of whom 198 were allocated to VR interventions and 159 to control groups. VR interventions lasted a mean of 13.3 (SD 7.7) weeks, with an average of 39.6 (SD 5.2) sessions lasting 25.3 (SD 5) minutes. Methodological quality was high in 5 studies (mean Physiotherapy Evidence Database score=5.6, SD 1.3). Four studies were included in the meta-analysis. Significant improvements were observed in balance, as measured by the Berg Balance Scale (MD=3.62; 95% CI 2.29‐4.95; PIPIPI ConclusionsVR-based home exercise interventions show promise in improving balance among older adults with frailty and prefrailty. However, their effects on strength and functional mobility remain unclear. Variability in study designs and outcome measures limits the generalizability of current findings. Further high-quality research is needed to determine optimal VR training protocols and assess long-term adherence and clinical effectiveness.